2014
DOI: 10.1177/1535370213520110
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CXCR2 signalling: A potential therapeutic target for preventing neutrophil-mediated inflammatory diseases

Abstract: Polymorphonuclear neutrophils (PMN) play a key role in host innate immune responses by migrating to the sites of inflammation. Furthermore, PMN recruitment also plays a significant role in the pathophysiology of a plethora of inflammatory disorders such as chronic obstructive pulmonary disease (COPD), gram negative sepsis, inflammatory bowel disease (IBD), lung injury, and arthritis. Of note, chemokine-dependent signalling is implicated in the amplification of immune responses by virtue of its role in PMN chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 92 publications
0
43
0
Order By: Relevance
“…Indeed, nothing is known in cancer patients of what the consequences of MDSC attraction and activation to form NETs could be. However, our results further argue in favor of the convenience of pharmacologically inhibiting IL8 as previously carried out in xenografted mouse models and currently in clinical trials with neutralizing antibodies (51) and small drug inhibitors (52).…”
Section: Discussionmentioning
confidence: 45%
“…Indeed, nothing is known in cancer patients of what the consequences of MDSC attraction and activation to form NETs could be. However, our results further argue in favor of the convenience of pharmacologically inhibiting IL8 as previously carried out in xenografted mouse models and currently in clinical trials with neutralizing antibodies (51) and small drug inhibitors (52).…”
Section: Discussionmentioning
confidence: 45%
“…CXCR2 and CXCR1 signaling plays key roles in neutrophil function, especially in chemotaxis, degranulation, phagocytosis and oxidative burst (Boppana et al, 2014). In our RA experimental model, we observed high levels of CXCL1/KC production and a reduction in the levels of this chemokine after oral pretreatment with ST-70.…”
Section: St-70 Inhibits Neutrophils Migration On Zymosan-induced Arthmentioning
confidence: 85%
“…A large body of work has explored the role of the chemokine (C-X-C motif) receptor 2 (CXCR2) during leukocyte recruitment to sites of inflammation [6], [15][19], [21][23]. Previous studies, utilizing the zebrafish model system, have shown that Cxcr2 receptor signaling axis is involved in both long-range systemic neutrophil mobilization from hematopoietic tissue as well as local recruitment to infection or purified Cxcl8 (IL-8, a potent Cxcr2 ligand) [17], [18].…”
Section: Introductionmentioning
confidence: 99%